The Effect of a Nurse-Led Multidisciplinary Team on Ventilator-Associated Pneumonia Rates - W. Bradley Dosher; Elena C. Loomis; Sherry L. Richardson; Jennifer A. Crowell; Richard D. Waltman; Lisa D. Miller; Muhammad Nazim; Faisal A. Khasawneh (Critical Care Research and Practice)
Background. Ventilator-associated pneumonia (VAP) is a worrisome, yet potentially preventable threat in critically ill patients. Evidence-based clinical practices targeting the prevention of VAP have proven effective, but the most optimal methods to ensure consistent implementation and compliance remain unknown. Methods. A retrospective study of the trend in VAP rates in a community-hospital’s open medical intensive care unit (MICU) after the enactment of a nurse-led VAP prevention team. The period of the study was between April 1, 2009, and September 30, 2012. The team rounded on mechanically ventilated patients every Tuesday and Thursday. They ensured adherence to the evidence-based VAP prevention. A separate and independent infection control team monitored VAP rates. Results. Across the study period, mean VAP rate was 3.20/1000 ventilator days ±5.71 SD. Throughout the study time frame, there was an average monthly reduction in VAP rate of 0.27/1000 ventilator days, P<0.001 (CI: −0.40–−0.13). Conclusion. A nurse-led interdisciplinary team dedicated to VAP prevention rounding twice a week to ensure adherence with a VAP prevention bundle lowered VAP rates in a community-hospital open MICU. The team had interdepartmental and administrative support and addressed any deficiencies in the VAP prevention bundle components actively.